The impact of economic inequality and gender parity on educational assortative mating: Evidence from the Luxembourg Income Study - David Monaghan (Luxembourg Income Study (LIS), 2014)
Though extensive research has described the prevalence of educational assortative mating, the causes of its variation across countries and over time is not well understood. Using data from the Luxembourg Income Study Database, I investigate the impact on marital sorting of both inequality between educational strata and increasing gender parity in the labor and educational markets. I find that in countries with greater returns to education, the odds of any sort of union that crosses educational boundaries is substantially reduced. However, there is only modest evidence of a relationship between returns to education and marital sorting within countries. I find that across countries, gender parity in educational attainment is related to reduced odds of female hypergamy and to increased odds of male hypergamy. Labor market parity between males and females appears to explain little of the variance in marital sorting by education either between or within countries.
Keywords: 330; assortative mating; inequality; gender parity; returns to education; cross-national research